Cleaning Efficiency of Amino‐Acid Surfactants with Polyoxyethylene Ether and Isopropanol in Liquid Carbon Dioxide. Issue 5 (3rd August 2018) - Wang, Zhanyan; Yu, Simiao; Wei, Junnan; Qiao, Weihong
Abstract: Although anionic surfactants have a distinct positive influence on the removal of particulate soil, the removal of particulate soils is insufficient in CO2 compared to perchloroethylene. A series of amino‐acid surfactants was selected as main surfactants to study the influence of polyoxyethylene ether and cosolvent on the cleaning effect. Glu‐C12 and C16(3) gave the best cleaning results, which increased from a detergency value of 4.6 when no surfactants were used to 8.32 when surfactants were used. In all experiments, charged anionic surfactant particles were formed, which are responsible for the removal of particulate soil from fabric by electrostatic repulsion. The use of a cosolvent (Isopropanol [IPA]) had a positive effect on the removal of particulate soil when using Glu‐C12 and TX‐45. However, for other compounding combinations, the addition of IPA had a negative effect on particulate soil removal. Of the cosolvents investigated, IPA was the most suitable. With the polarity of the system increasing after adding IPA, the ethylene oxide groups of TX‐45 were partially extended to CO2 . Through the steric effects of branched methyl groups, the cleaning effect was improved.